NEW PROFILE MODIFICATION METHOD OF NON⁃UNIFORM MESHES BASED ON SHAPE FUNCTION - LIU Meng; GANG XianYue; CHE YeJun; MENG Peng; ZHANG Fan (Jixie qiangdu)
A new profile modification method of non⁃uniform meshes was proposed to solve the problem of premature failure of mechanical components due to uneven contact pressure distribution.Based on the element shape function and"virtual nodes",a formula was developed to formulate the mechanical relation between the contact nodes of the non⁃uniform mesh,a mathematical equation was derived to formulate the correspondence between the node modification and the contact pressure,and a minimax model was developed to solve the modification by minimizing the maximum contact pressure.In order to improve global convergence and computational efficiency of the modification calculation,the minimax model was transformed into a linear programming model.The applicability and effectiveness of this new profile modification method for general elastic contact modification problems was verified by three elastic contact modification examples.